2011
DOI: 10.1177/0883911511423563
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion and proliferation enhancement by gelatin nanofiber scaffolds

Abstract: Gelatin nanofibers (GNs) prepared by electrospinning were cross-linked with glutaraldehyde vapor to improve their water-resistant ability. After cross-linking treatment, the form of the fibers expressed no substantial change, but the average diameter of the fibers increased with increasing cross-linking time. The swelling induced by the moisture during the cross-linking process was moderated when the cross-linking time reached 45 min. The contact angle measurements confirmed that the electrospun gelatin fibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
86
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(89 citation statements)
references
References 34 publications
2
86
1
Order By: Relevance
“…However, biomaterial activity is still one key factor in designing an artificial bioscaffold (Kakisis et al 2005). To achieve that aim, numerous methods have been carried out (Ma et al 2005;Gouma et al 2010;Wu et al 2011;Truong et al 2012;Wang et al 2012). Among these methods, loading specific particulates was thought to be a facile one.…”
Section: Introductionmentioning
confidence: 99%
“…However, biomaterial activity is still one key factor in designing an artificial bioscaffold (Kakisis et al 2005). To achieve that aim, numerous methods have been carried out (Ma et al 2005;Gouma et al 2010;Wu et al 2011;Truong et al 2012;Wang et al 2012). Among these methods, loading specific particulates was thought to be a facile one.…”
Section: Introductionmentioning
confidence: 99%
“…Biopolymer-based materials resembling components of the extracellular matrix (ECM), like collagen or gelatin, are promising candidates for soft tissue regeneration since they provide recognition motifs for cell adhesion and differentiation and are degradable under physiological conditions [1]. Current clinical applications of collagen or chemically modified collagen rest on its advantages of being tissue compatible and available from natural resources [2], but also display drawbacks as immunogenic responses [3], difficulty to tailor mechanical properties [4], and limitations in retaining dimensional stability.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that cross-linking of gelatin microspheres with GA takes place more rapidly and is more efficient than with genipin. A maximum crosslinking degree of approximately 90 % is achieved in less than 4 hours of exposure to GA, whereas just around 60 % of cross-linking was achieved after 72 h of exposure to genipin [21,22].…”
mentioning
confidence: 99%